Dissident practices Brazilian women artists, 1960s-2020s - Calirman, Claudia (Duke University Press, 2023)
"In Dissident Practices, Claudia Calirman examines sixty years of visual art by prominent and emerging Brazilian women artists from the 1960s to the present, covering the period from the military dictatorship to the return to democracy in the mid-1980s, the social changes of the 2000s, the rise of the Right in the late-2010s, and the recent development of an overtly feminist art practice. Though they were lauded as key figures in Brazilian art, these artists still faced adversity and constraints because of their gender. Although many of them in the 1960s and 1970s disavowed the term feminism, Calirman gives a nuanced account of how they responded to authoritarianism, engaged with trauma in the aftermath of the military dictatorship, interrogated social gender norms, and fought against women's objectification. By battling social inequalities, structures of power, and state violence, these artists create political agency in a society where women remain targets of brutality and discrimination"--